PRACTICE-ORIENTED EDUCATIONAL PROGRAM OF ACTIVITIES OF THE CHILDREN ENVIRONMENTAL ASSOCIATION AS A TOOL TO FORM THE SEVENTH AND EIGHTH-GRADERS’ ENVIRONMENTAL RESPONSIBILITY - A. Loshchilova, Anna (Nuances: estudos sobre Educação, 2019)
The Article covers the problem of forming form the seventh and eighth-graders’ environmental responsibility in additional (informal education), which is caused by focus of the modern education on forming  the environment-orientated moral personality qualities, which can assure the switching of the society over to the sustainable development; by significant possibilities of the children environmental associations in developing the  environmental responsibility, and the lack of scientifically substantiated, approbated practice-oriented programs favoring the solution to this problem. The article is aimed at substantiating the specificity of a goal, content-related, procedural and technological components of the program of activities of the children environmental association “My environmental responsibility: to the co-creation with the nature”; opening of the pedagogical раскрытие педагогического tools of diagnostics of its efficiency, presentation of results of the program implementation in the educational practice.   As the leading theoretical methods, simulation and designing were used, which make it possible to develop the key structural components of the program.     The basic empirical method of the research is a pedagogical experiment, during which the program efficiency was diagnosed in terms of criteria and indicators of maturity of the environmental responsibility components with 210 members of the children environmental associations at the age from 11 to 14 years old.    The article considers the theoretical and methodological basis of the program, which includes the ideas of ecohumanism, coevolution and sustainable development; an axiological, personal-activity and ecopsychological approaches, which provide for an organization of the developing ecology-оriented educational environment of the children association as a tool of  forming the environmental responsibility. The article presents the program content, which consists of two components (external and internal components), discusses the succession of forming the environmental responsibility, which includes four stages and substantiates a technology of forming the environmental responsibility in the children association, which is presented by a system of environmentally responsible businesses. The article materials are of practical value to school teachers, additional education teachers, students of pedagogical specialties and advisers of children environmental associations.